Implementasi metode SDLC pada aplikasi media interaktif “EcoWatt” berbasis WebGL - Adiguna, Yogatama; Purwanto, Agus; Laksmita, Nadea Cipta (AI Society & STMIK Indonesia, 2024)
Electrical energy is derived from the movement of electric charges due to a potential difference. Beyond housing, clothing, and food, electricity is a fundamental necessity, providing not only illumination but also powering various daily activities. Indonesia is rich in both fossil and renewable energy sources. However, the focus has predominantly been on fossil fuels, despite the fact that the electricity sector contributes 31% to global greenhouse gas emissions. Renewable energy, such as biomass, wind, water, and solar, offers sustainable alternatives. To foster early understanding and innovation in alternative energy, the author has developed